1999
DOI: 10.1103/physrevb.59.r12763
|View full text |Cite
|
Sign up to set email alerts
|

Optical transmission through metal films with a subwavelength hole array in the presence of a magnetic field

Abstract: In a recent paper Ebbesen et al. ͓Nature ͑London͒ 391, 667 ͑1998͔͒ reported on extraordinary optical transmission through periodic hole arrays in metallic films. They explain this by the coupling of light with surface plasmons. Continuing this idea, we have studied such systems in the presence of a static magnetic field. The problem is treated in the quasistatic limit, i.e., when the wavelength is larger than the hole sizes and the array period. We find that the frequency of the transmission peak depends stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 13 publications
2
72
2
Order By: Relevance
“…One of the prominent features of such materials is the effect of the extraordinary optical transmission (EOT), which has been revealed and extensively studied in the past several years [1,2]. However, magnetooptics of plasmonic systems with the EOT phenomenon has been considered so far only in several works [3,4], and no pronounced MO effects increase was found. Experiments on Co films perforated by the periodic subwavelength hole arrays revealed that the MO Kerr effect in the spectral range of the anomalous transmission band is even about one order smaller than in uniform Co films of the same thickness [4].…”
mentioning
confidence: 99%
“…One of the prominent features of such materials is the effect of the extraordinary optical transmission (EOT), which has been revealed and extensively studied in the past several years [1,2]. However, magnetooptics of plasmonic systems with the EOT phenomenon has been considered so far only in several works [3,4], and no pronounced MO effects increase was found. Experiments on Co films perforated by the periodic subwavelength hole arrays revealed that the MO Kerr effect in the spectral range of the anomalous transmission band is even about one order smaller than in uniform Co films of the same thickness [4].…”
mentioning
confidence: 99%
“…The MMD has optical properties based on the periodic structures of microscopic holes. [1][2][3] The MMD transmits electromagnetic waves of specific frequency (wavelength) in the terahertz region, corresponding to the period of the through holes, which act like a band-pass filter. 4 The specific optical properties of MMD have been reported since the 1960s.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetooptics of plasmonic structures has been considered only in several works so far [10,11]. In Ref.…”
mentioning
confidence: 99%